Analysis of English lecturer assessment using academic information system (SIAKAD) institution - Tira Nur Fitria (Journal of Applied Studies in Language, 2023)
This research describes the English lecturer’s assessment by students in odd semesters in the 2022/2023 academic year using Academic Information System. This research is descriptive qualitative research. This research uses data from questionnaire results from SIAKAD or Sistem Informasi Akademik Institut Teknologi Bisnis AAS Indonesia at siakad.itbaas.ac.id. The finding shows that ITB AAS implements monitoring of lecturers in carrying out their teaching duties by allowing students to fill out questionnaires “Lecturer Assessment by Students” by filling in SIAKAD, especially in the odd semester of 2022. Students must fill in a value, which ranges from 0-4, each questionnaire consisting of 43 questions. The questions used for obtaining lecturer assessments by students in the form of a checklist regarding lecturer performance in daily lecture activities in odd semesters 2022/2023 include aspects of lectures including planning, implementation, evaluation, and lecturer’s personality. There are 32 students from S1 Accounting study program fulfill the questionnaire. From the questionnaire, it is obtained an average rating of 3.83 on a scale of 0-4 or with “Very Good” criteria. It also shows that most dominant students choose the score (4) which shows the students perceive positively about English lecturers in the teaching and learning process. The further research needs to be implemented to know more classes and students about their ‘perception’ toward the English Language Teaching (ELT) process during one semester.